Strategies for inhibiting anode dendrite growth in lithium–sulfur batteries. Issue 9 (21st February 2020) - Luo, Yaqiu; Guo, Linli; Xiao, Min; Wang, Shuanjin; Ren, Shan; Han, Dongmei; Meng, Yuezhong
Abstract : Recently, lithium–sulfur batteries have attracted considerable attention due to their high theoretical specific capacity and high energy density. In this paper, we summarize the strategies of lithium anode improvement formulated in recent years. Abstract : Recently, lithium–sulfur batteries have attracted considerable attention due to their high theoretical specific capacity (1673 mA h g −1 ) and high energy density (2800 W h kg −1 ), which is regarded as the most promising next-generation energy used for portable electronic devices, vehicles, and energy storage systems. However, there are still some problems that persist for the practical applications of lithium–sulfur batteries; in particular, the problems caused by lithium dendrite growth can seriously hinder the real-world applications and development of lithium–sulfur batteries. In this paper, we summarize the strategies of lithium anode improvement formulated in recent years, and we introduce them in sufficient progressive order on the basis of three aspects: anode surface modification, anode modification, and anode structure design. Nevertheless, the growth of lithium dendrites is still a formidable problem, and we have to continue devoting time and energy toward addressing this issue.